'Let's be friends'; exploring governance, crime precipitators and public safety in the night-time economies of Cardiff (Wales) and Perth (Australia). Issue Volume 12:Issues 2(2019) (3rd April 2019) - Cozens, Paul; Greive, Shane; Rogers, Colin
ABSTRACT: There are tensions between agencies seeking to restrict and control the night-time economy (NTE) and those focused on promoting it. These tensions need to be inspected. Using perspectives from environmental criminology it has been hypothesized that planning governance issues, relating to the provision of public transport, taxis services and public toilets, may act to precipitate crime and disorder and exacerbate public safety issues. Utilising research findings from a study of regular users of the NTE's of Cardiff (UK) and Perth (Australia), we test this hypothesis. The research findings suggest that the most appropriate manner in which to deal with crime and disorder in the NTE is through inter-agency partnership approaches involving the users of the NTE. This approach refocusses the debate to explore the positive elements of the NTE we do want. This contrasts with many contemporary approaches focused solely on the negative aspects of the NTE we don't want.